FAKTOR–FAKTOR YANG MENYEBABKAN TERJADINYA AUDITOR SWITCHING (Students' Journal of Accounting and Banking, 2015)
This research investigates the factors that cause the switching auditor’s. This research was conducted in the Indonesia Stock Exchange using manufacturing companies that have gone public. The sampling method is using purposive sampling with the research period 2011-2013. It was acquired 76 companies for sample of each year with the total testing sample are 228 companies (3 years). Hypothesis testing is done by logistic regression method. The test result of study hypothesis indicates that the audit opinion, change management, external auditor’s, the company’s growth has no significant effect the switching auditor’s, while testing a significant effect on the size of the company switching auditor’s.Keywords: Audit Opinion, Change Management, External Auditor’s, The Company’s Growth and Size Of The Company